2019
DOI: 10.1002/jcb.27615
|View full text |Cite
|
Sign up to set email alerts
|

Dachengqi decoction alleviates acute lung injury and inhibits inflammatory cytokines production through TLR4/NF‐κB signaling pathway in vivo and in vitro

Abstract: Background and Objectives: Sepsis that arises from uncontrolled pulmonary inflammation could induce acute lung injury (ALI), leading to the high death rate. Dachengqi decoction (DCQD) is a common traditional Chinese herbal medicine with strong anti-inflammatory effects. The current study aimed to explore the effect of DCQD on the inflammatory cytokines production, the aquaporin-1 (AQP-1) and AQP-5 protein expression in lipopolysaccharide (LPS)-induced ALI models, and the potential mechanisms underlying its eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 25 publications
(47 reference statements)
2
22
0
Order By: Relevance
“…TLR4 is a target of miR-93 in RAW264.7 cells. According to previous research, TLR4 is a common receptor of LPS, and plays important roles in the inflammatory response in ALI (38)(39)(40)(41)(42). Through bioinformatics prediction using TargetScan 7.0 and miRanda, the present study found that miR-93 directly targeted the TLR4 gene and that the target sequences were highly conserved among species (Fig.…”
Section: Mir-93 Attenuates Lps-induced Ali In Micesupporting
confidence: 56%
“…TLR4 is a target of miR-93 in RAW264.7 cells. According to previous research, TLR4 is a common receptor of LPS, and plays important roles in the inflammatory response in ALI (38)(39)(40)(41)(42). Through bioinformatics prediction using TargetScan 7.0 and miRanda, the present study found that miR-93 directly targeted the TLR4 gene and that the target sequences were highly conserved among species (Fig.…”
Section: Mir-93 Attenuates Lps-induced Ali In Micesupporting
confidence: 56%
“…4,5 Several types of studies have confirmed that continued LPS can contribute to severe acute or long-lasting lung impairment, such as lung ultrastructural changes, restoration, and pulmonary functional disorder, which is more critical than that formed through LPS itself. 6,7 Results have confirmed that LPS-induced cell apoptosis occurs because of damage from the sudden release of subsequent reactive oxygen species, which plays a crucial role in LPS-induced ALI. 8 Numerous cascades control apoptosis (a type of automatic cell death).…”
Section: Introductionmentioning
confidence: 81%
“…reported that the inhibition of the TLR4 signaling pathway suppressed the production of inflammatory cytokines, thereby improving ALI in rats (28). He et al demonstrated that the LPS/TLR4 axis can activate the NF-κB signaling pathway, resulting in inflammatory cell infiltration (44).…”
Section: Discussionmentioning
confidence: 99%
“…3A and B, TLR4 was identified as a potential target gene of miR-17, with the target site located in the 3'-UTR of TLR4 mRNA. It is well known that TLR-4 is a common receptor of LPS, and its downstream signaling effector, NF-κB, is closely associated with inflammatory response in ALI (14,(27)(28)(29)(30). Thus, TLR4 was selected for the subsequent investigation.…”
Section: Tlr4 Is a Direct Target Of Mir-17mentioning
confidence: 99%